Electromagnetic lump soliton solution of (2 + 1) dimensional ferromagnetic nanowire with Dzyaloshinskii-Moriya interaction. (2020) - Pavithra, T.; Ravichandran, R.; Sunny, Geo; Kavitha, L.
Abstract: Influenced by the modern experiments on spin chain materials to CoPt3 nanowire system, we theoretically examine the dynamics of ferromagnetic nano-wire with Dzyaloshinskii-Moriya interaction. This classification is described with a background inthe Landau - Lifshitz - Gilbert equation. We analytically develop the electric field illustrations of both lump soliton and soliton collision interactions. Similarly, we designate this system aiming at the related parametrically (2 + 1) dimensional equation employing generalized unified method and give an estimated systematic solution that defines the soliton collision interaction. Furthermore, we establish that the soliton can be confined to nanowire system with a suitable condition.